A reforma trabalhista: modernização das relações de trabalho ou uma política pública perversa? - Costa, Antônio Célio Martins Timbó (2024)
The reform of labor legislation, commonly called labor reform, was presented to Brazilian society, by the Temer government, as a panacea for all ills. It would essentially be an instrument to contain unemployment, which has shown increasing rates since the 2015 economic crisis. It would also serve to modernize labor relations which, according to its defenders, were archaic, as they were still shaped by the framework of the Consolidation of Labor Laws (CLT), dated 1943. Academic studies on the reform have demonstrated, however, that its vaunted objectives of labor reform were not achieved. In fact, there is no data that allows us to conclude that unemployment rates have decreased. On the contrary, unemployment increased in the period after the labor reform. Labor Reform: Modernization of Labor Relations or a Perverse Public Policy? The work has the following general objective: to evaluate in depth the 2017 labor reform, from the perspective of trade unions. Its specific objectives are the following: (i) analyze what the characteristics of the so-called welfare state would be; (ii) present the difficulties in building the welfare state in Brazil, from the perspective of the world of work, pointing out labor reform as one of these difficulties; (iii) carry out a content analysis of the labor reform, from the perspective of trade unions; (iv) analyze the institutional trajectory of labor reform, from the perspective of trade unions; (v) delimit the temporal and territorial spectrum of labor reform, from the perspective of trade unions; and (vi) analyze the context of labor reform, from the perspective of trade unions, placing the reform within the environment of precarious labor relations, resulting from neoliberalism. As a research problem, the following question is raised: to what extent does the labor reform compromise the functioning of trade unions in the State of Ceará? This work intends precisely to launch parameters for the evaluation of labor reform, presenting its regulations; raising political, social and economic aspects related to its implementation and, finally, analyzing it based on its content, its institutional trajectory, its temporal and territorial spectrum and its context